Innovation of Islamic Education (Multisite Study at Madrasah Aliyah Pesantren Al-Amin and Madrasah Aliyah Darul Hikmah, Mojokerto Regency) - Sholikhin, Anwar (Journal of World Science, 2023)
Quality educational institutions produce graduates who are superior and useful to society. Excellent graduates are produced from a quality learning process. To improve the quality of educational institutions, creativity and innovation are needed in the learning process. This study aims to identify and analyze Islamic Education Innovation (Multisite Study at MA Islamic Boarding School Al-Amin and MA Darul Hikmah, Mojokerto Regency). data collection techniques through in-depth interviews, observation, and documentation Data were analyzed iteratively through single-site and multi-site analysis. credibility, transferability, dependability, and confirmation. This study resulted in: (1) Innovation programs in the form of developing student potential through the Leadership Program, Religious Programs, Multistrategy Programs, Intrapreneurship Programs, Bilingual Programs, integration programs, TPQ teacher candidate training programs, (2) Innovation design in a) includes four critical thinking skills, creative, communicative and collaborative, b) implementation of the concept of khoirunnas anfauhum line; (3) Innovation steps in the learning process include knowledge and implementation; (4) the Islamic education innovation model, namely the bottom-up model that applies an integrated curriculum and experiential learning. This research is an Islamic Education Innovation, namely learning based on the benefits for students, where the formulation combines an integrated curriculum with experiential learning.